TEACHING METACOGNITIVE SKILLS TO ADULT LEARNERS - Kim N.P.; Kandalina Y.M. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article focuses on the theoretical foundations of andragogy and the importance of developing metacognitive skills among adult learners. It reviews current research and instructional approaches that enhance planning, self-monitoring, and reflection in adult education. The findings highlight the need to integrate metacognitive strategies into adult learning processes to increase autonomy and learning effectiveness.
Keywords: andragogy; adult learners; metacognitive skills; self-regulated learning; reflection